Nectar production of pear (Pyrus communis L.) cultivars - P. Benedek; G. Kocsisné Molnár; J. Nyéki (International Journal of Horticultural Science, 2000)
Detailed studies were made on the nectar production of 44, 16 and 18 pear cultivars, respectively, in a cultivar collection of pear during three consecutive years with highly different weather in the blooming. Results clearly show that pear does not necessarily produce small amount of nectar as stated in the world literature. In fact, pear can produce extremely high amount of nectar sometimes much higher than other temperate zone fruit trees species but its nectar production is highly subjected to weather, first of all to air temperature. Low nectar production seems to be more frequent than high one and cold weather can prevent its nectar production at all. On the other hand, results corroborate to the earlier statements on the low sugar concentration of pear nectar. There is a highly significant negative correlation between the amount of nectar produced by pear flowers and its sugar concentration (r = -0.52, n = 291, p< 0.001 for 1996, r = -0.34, n = 197, p< 0.001 for 1998). Sugar concentration in individual flowers may be up, to 40% in exceptional cases but generally it is well below 20%. Very high figures for sugar concentration in pear nectar at the literature seem to be incomprehensible. In contrast of some earlier statement in the literature no real difference could be established in the nectar production of pear cultivars, based on much more measurements than in earlier studies. Very low sugar concentration in pear nectar can explain the fact that the overwhelming majority of honeybees are pollen gatherers at pear trees even in the case of exceptionally high nectar production.